Qualidade de vida e a relação da whoqol-bref com a terapia ocupacional - Matos, Camilla Souza (2023)
The term Quality of Life is marked by several concepts that outline its pillars and one of these concepts is that Quality of Life is the individual's perception of their position in life and in relation to their goals and perspectives. From this, tools were created with the objective of studying and measuring the Quality of Life, where the WHOQOL-Bref stands out, a questionnaire that evaluates how the subject observes and understands his quality of life from a range of facets classified within domains , where it is possible to observe positive and negative issues that imply the subject's Quality of Life and their daily life, which is filled with occupations, work tools and Occupational Therapy intervention. In this context, the objective of this work was to understand the concepts and vision of Quality of Life and Occupational Therapy using the WHOQOL-Bref tool and its domains. Data were collected from databases and reliable sources, resulting in studies that used the WHOQOL-Bref and the term Quality of Life